Construction of high-efficient class D power amplifiers - Andreev, Anatoliy; Soloduhin, Vitaliy; Semenov, Artur (Видавництво Львівської політехніки, 2010)
The amplifiers of class D with pulse with modulation (PWM) which work in the mode of tracing are are analyzed. The transfer functions of closed, combined, two-connected and iterated systems are obtained. Application amplifiers with combined, two-connected, iterated control allow the astatism order of an.
Keywords: amplifiers of class D; closed; combined; two-connected and iterated systems; astatism